2007
DOI: 10.1093/her/cym049
|View full text |Cite
|
Sign up to set email alerts
|

Storage of household firearms: an examination of the attitudes and beliefs of married women with children

Abstract: Although safe firearm storage is a promising injury prevention strategy, many parents do not keep their firearms unloaded and locked up. Using the theory of planned behavior as a guiding conceptual framework, this study examines factors associated with safe storage among married women with children and who have firearms in their homes. Data come from a national telephone survey (n=185). We examined beliefs about defensive firearm use, subjective norms, perceived behavioral control and firearm storage practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Such results are encouraging because, while not all firearms within each reporting household may have been locked or unloaded, participants were at least indicating awareness that storage methods are needed and are being used for some of their firearms. Overall, our results appeared consistent with previous research that a portion of households containing firearms can be expected to contain some that are loaded and unlocked (e.g., Schuster, 2000), that there are significant variations in storage practices , and that a large portion of households can be expected to contain at least some firearms secured in a safe manner (e.g., Johnson et al, 2008).…”
Section: Demographic Factorssupporting
confidence: 90%
See 4 more Smart Citations
“…Such results are encouraging because, while not all firearms within each reporting household may have been locked or unloaded, participants were at least indicating awareness that storage methods are needed and are being used for some of their firearms. Overall, our results appeared consistent with previous research that a portion of households containing firearms can be expected to contain some that are loaded and unlocked (e.g., Schuster, 2000), that there are significant variations in storage practices , and that a large portion of households can be expected to contain at least some firearms secured in a safe manner (e.g., Johnson et al, 2008).…”
Section: Demographic Factorssupporting
confidence: 90%
“…One study reported that a large portion of households appear to store firearms unloaded (63%) and ammunition was stored separately (69%), but nearly half did not store firearms in a locked fashion, and some (18%) stored a firearm unlocked and loaded (Coyne-Beasley, Schoenbach, & Johnson, 2001). In a more recent study, 93% of participants reported that the firearm in question during an interview was stored locked and unloaded (Johnson, Runyan, Coyne-Beasley, Lewis, & Bowling, 2008). Thus, safe storage practices are used in some homes, but the overall pattern of storage practices varies considerably across households.…”
Section: Firearms Storage Practicesmentioning
confidence: 99%
See 3 more Smart Citations